Cross-National and Multi-Language Qualitative Research: Challenges and Recommendations. (July 2013) - Haak, Maria; Himmelsbach, Ines; Granbom, Marianne; Löfqvist, Charlotte
Interest in cross-national partnership is increasing in Europe, a situation very much reflected in calls for funding. Multi-language qualitative research methodologies need to be strengthened in order to support this growing trend toward the promotion of cross-national collaboration. This practice analysis reports on our experience of carrying out cross-national and multi-language based qualitative research. Based on this, we recommend taking into account the potential challenges of language and national culture from the planning phase onwards, handling them in a structured, predefined way throughout the research process and using software to assist with the challenges brought about in a multi-language environment.